Digitalisasi Manajemen Keuangan Pesantren melalui Implementasi Aplikasi CARDS - Maela, Siti Nur Maela; Hanif, Muh. (Media Manajemen Pendidikan, 2025)
Financial management in Islamic boarding schools (pesantren) often faces complex challenges, such as weak accountability systems and the potential for fund misuse. Therefore, technological innovation is needed to create more effective, efficient, and transparent financial governance. The CARDS application emerges as a solution—a digital financial management information system integrated within pesantren. This research employs a qualitative approach using a case study method at two pesantren: Az Zahra Al Gontory and Al-Qur’an Al Yusufiyah. Data collection techniques include interviews, observations, and document analysis involving administrators, application admins, developers, students, and student guardians. Data analysis was conducted using the Miles and Huberman model, with validity tested through triangulation, member checks, and audit trails. The findings show that the CARDS application positively impacts pesantren financial management by improving the efficiency of record-keeping, accelerating reporting, simplifying daily financial control, and providing real-time data access. From the user perception perspective, the application is considered easy to use due to its simple interface design, practical operation, and minimal technical issues thanks to developer support. Overall, the implementation of this application supports the principles of Good Financial Governance by strengthening transparency, accountability, and active participation, thereby promoting a professional, modern, and digitally relevant financial management system in pesantren. Keywords: Financial Management, Pesantren, CARDS Application, Good Financial Governance, Technology Acceptance Model